DETERMINANTS OF PROFITABILITY OF INSURANCE COMPANIES IN INDONESIA (CASE STUDY ON AN INSURANCE COMPANY LISTED ON THE INDONESIAN STOCK EXCHANGE) - Reni Marlina, (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
Insurance as one of the Non-Bank Financial Industries (IKNB) plays an important role in the economy and must perform well and be healthy. Profitability is one of the most important things to assess the performance of an insurance company. This study aims to determine the determinants of the profitability of insurance listed on the Indonesia Stock Exchange. This research uses multiple linear regression method. The dependent variable is Return On Assets (ROA) and the independent variable is Liquidity, Leverage, Claim Expenses, Premium Income and Company Size. The conclusion is that partially premium income has a significant effect on profitability and simultaneously liquidity, leverage, claims expense, premium income and company size have an effect on insurance company profitability.